From Micro to Macro: The Combination of Consciousness - Young, Asa; Robbins, Isabella; Shelat, Shivang (Frontiers in Psychology, 2022)
The synchronization of neural rhythms between different individuals is a relatively recent discovery with potentially profound implications for the disciplines of neuroscience and philosophy. The established “joint attention” account explains this interpersonal neural synchrony (INS) through group entrainment to a shared attended stimulus. The current paper expands upon this account by applying General Resonance Theory (GRT) axioms and conjectures in exploring the possibility of micro-to-macro consciousness combination of distinct individuals. Our account relies on various types of shared resonance, but the fundamental shared resonance relied upon is shared EEG rhythms (i.e. shared electromagnetic field oscillatory frequencies). An identical framework of micro-to-macro resonant combination between the distant neural clusters of the central and peripheral nervous systems is reviewed and rearticulated for this purpose. It is our hypothesis that the current literature supports our model of interpersonal resonant combination. An empathetically-related group synchronized by entraining behavioral rhythms, engaging in cooperative activity, possesses the greatest potential for such a phenomenon, also known as “group flow.” We examine various types of entrainment signals that may result in specific boundaries for the emerging macro-scale cognitive system. We also examine INS-associated cognitive exhibits and the likely occurrence of a GRT phase transition that may distinguish merged versus aggregate groups. The establishment of a concrete account of the combination of consciousness at a scale superseding individual human consciousness remains speculation, but our suggested approach provides a framework for empirical testing of these possibilities.